2019
DOI: 10.1021/acsami.9b15596
|View full text |Cite
|
Sign up to set email alerts
|

Aroma Molecules as Dynamic Volatile Surfactants: Functionality beyond the Scent

Abstract: Understanding of non-equilibrium processes at dynamic interfaces is indispensable for advancing design and fabrication of solid state and soft materials. The research presented here unveils specific interfacial behavior of aroma molecules and justifies their usage as multifunctional volatile surfactants. As non-conventional volatile amphiphiles we study commercially available poorly water-soluble compounds from the classes of synthetic and essential flavor oils. Their distinctive feature is high dynamic interf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…This leads to an increased concentration of the surfactant in the pendant drop. 24 For the solution with a higher concentration than the CMC, the surface tension is constant since the minimum value of the surface tension, and accordingly, maximum adsorption was attained at the time scale of subseconds.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This leads to an increased concentration of the surfactant in the pendant drop. 24 For the solution with a higher concentration than the CMC, the surface tension is constant since the minimum value of the surface tension, and accordingly, maximum adsorption was attained at the time scale of subseconds.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We note, however, that fast adsorption dynamics of volatile amphiphiles, with a significant decrease in the surface tension happening in the μs range, cannot be satisfactorily fitted with the standard Ward−Tordai model. 24 Also, most of the reported evaluations of the dynamic data covered adsorption kinetics at a 1−100 s time scale, while reliable measurements of adsorption dynamics in the microsecond range remain an experimental challenge. 3,37,38 Evaporation Behavior of Volatile Surfactants.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface activities of flavor molecules have recently received more attention. A study by Soboleva et al (2019) has revealed the surfactant nature of other flavor molecules (e.g., citral, linalool, geraniol) and the volatility of these compounds is considered beneficial in some industrial processes. Coffee oil has also been studied for its surfactant properties (Deotale et al, 2019).…”
Section: Effect On Surface Tensionmentioning
confidence: 99%